Apakah Good Corporate Governance Memoderasi Hubungan Kecenderungan Kecurangan Manajemen terhadap Fraudulent Financial Statement? - Reskino Reskino; Mulia Saba Bilkis (Universitas Swadaya Gunung Jati, 2022)
AbstractThis study aims to examine the effect of management fraud tendencies as proxied by the fraud triangle dimensions (pressure, opportunity, rationalization) on fraudulent financial statements as proxied by earnings management, with good corporate governance as a moderating variable. BUMN listed on the Indonesia Stock Exchange for the period 2017-2021 is the population in the study. Purposive sampling became the sampling technique used in the study and obtained as many as 95 units of sample data. Based on the tests conducted using SmartPLS, it can be concluded that of the three elements of the fraud triangle, only pressure and opportunity have a significant influence on fraudulent financial statements. Meanwhile, the rationalization has not been able to contribute significantly to fraudulent financial statements. It seems that rationalization is the tendency of management to commit fraud. Furthermore, good corporate governance has not been able to strengthen or weaken the relationship between the tendency of management fraud and fraudulent financial statements. The results of this study can be used as valuable feedback to reduce the tendency of management fraud in BUMN.Keywords: Good corporate governance; Earning management; Fraudulent financial statement; Pressure; Opportunity; RationalizationÂ AbstrakPenelitian ini bertujuan untuk menguji pengaruh faktor kecenderungan kecurangan manajemen yang diproksikan dengan dimensi triangle fraud (pressure, opportunity, rationalization) terhadap fraudulent financial statement yang diproksikan dengan earnings management, dengan good corporate governance sebagai variable moderasi. BUMN yang tedaftar di Bursa Efek Indonesia periode 2017-2021 adalah populasi dalam penelitian. Purposive sampling menjadi teknik pengambilan sampel yang digunakan dalam penelitian dan memperoleh sebanyak 95 unit data sampel. Berdasarkan pengujian yang dilakukan dengan menggunakan SmartPLS maka dapat disimpulkan bahwa dari tiga elemen fraud triangle hanya pressure dan opportunity yang memiliki pengaruh signifikan terhadap fraudulent financial statement. Sementara rationalization belum mampu berkontribusi secara significant terhadap fraudulent financial statement. Selanjutnya Good corporate governance belum mampu memperkuat maupun memperlemah hubungan antara kecendrungan kecurangan manajemen dengan fraudulent financial statement. Hasil penelitian ini dapat digunakan sebagai umpan balik yang berharga untuk menurunkan kecendrungan kecurangan manajemen di BUMN.Kata kunci: Kecurangan laporan keuangan; Manajemen laba; Peluang; Rasionalisasi; Tata kelola perusahaan; Tekanan